Relationship of mid-parental height, Calcium intake, and intensity of physical activity with body height growth of high school students in Malang - Arif Kusuma Firdaus; Anung Putri Illahika; Annisa Hanifwati; Hanna Cakrawati (Universitas Muhammadiyah Surabaya, 2023)
Abstract Â Stunting is one of Indonesia's problems, as portrayed in RISKESDAS 2018. This means the growth of Indonesian children was not optimal. Some factors that might affect body height growth were genetic factors, represented by mid-parental height, nutritional factors, especially calcium, and physical activity, which could activate pathways to stimulate growth. These factors were known to have a huge role in body height growth, especially if these factors were optimized in adolescence, as in high school students. This research aimed to explain the relationship between body height growth and the factors that might affect it: mid-parental height, calcium intake, and the intensity of physical activity. This research was observational analytic, using purposive sampling as the sampling method and collecting data using a cross-sectional questionnaire. Statistical analysis between variables shows that mid-parental height was positively related (p<0.05, r: 0,356), while calcium supplementation was not associated (p<0.05, r: -0.165), and intensity of physical activity was not related (p=0.059, r: 0.089) with the body height growth of the students. In conclusion, among the factors that were analyzed, mid-parental height was the only one that had a relationship with body height growth.